The Effectiveness of Bottom-Up And Topdown Approaches In The Reading Comprehension Skill For Junior High School Students - Ardhani, Raden Rara Vivy Kusuma (English Education Department, Universitas Islam Indonesia, 2011)
Reading skill is taught in all level of education in Indonesia and it includes Junior High School. The standard of competence and basic competences of students' reading skills in the second semester of eighth grade SMP are to understand the meanings in simple short essays recount and narrative form. However, there are four main problems faced by the students in reading comprehension, such as finding general idea of a text, identifying the meaning of the word, finding main ideas and information. This situation is caused by several factors such as low motivation, limited vocabulary and monotonous teaching. This paper will discuss about the effectiveness of two reading approaches, they are bottom-up and top-down approach. The discussion will describe the concept of the approaches and the application of the approaches in the classroom by using experimental research.